Colloquial Urdu : the complete course for beginners - Bhatia, Tej K.; Koul, Ashok (London ; New York : Routledge, 2013)
This book provides a step-by-step course in Urdu as it is written and spoken today. Combining a user-friendly approach with a thorough treatment of the language, it equips learners with the essential skills needed to communicate confidently and effectively in Urdu in a broad range of situations. No prior knowledge of the language is required. Key features include: progressive coverage of speaking, listening, reading and writing skills structured, jargon-free explanations of grammar an extensive range of focused and stimulating exercises realistic and entertaining dialogues covering a broad variety of scenarios useful vocabulary lists throughout the text additional resources available at the back of the book, including a full answer key, a grammar summary, bilingual glossaries and English translations of dialogues. This second edition has been extensively updated and revised throughout, with particular attention to the Urdu script - coverage is now integrated throughout the book and the script font has been enlarged and improved. Balanced, comprehensive and rewarding, Colloquial Urdu will be an indispensable resource both for independent learners and for students taking courses in Urdu.
Includes bibliographical references and index.
Keywords: Urdu language -- Textbooks for foreign speakers -- English; Urdu language -- Spoken Urdu; Urdu language -- Self-instruction.; Urdu language -- Sound recordings for English speakers; Urdu language; Urdu language -- Spoken Urdu; Instructional and educational works; Self-instruction.; Sound recordings -- for English speakers; Textbooks; Textbooks -- for English speakers